Part I. Meridian-Scanning Photometric System for Proton Auroras and Electron Auroras (Constitution of Proton Aurora and Electron Aurora Substorms) (AERONOMY) - FUKUNISHI, Hiroshi; TOHMATSU, Takao (1973)
P(論文) A meridian scanning photometric system was designed for the simultaneous observation of the dynamic behavior of the proton and electron auroras with high time resolution. The hydrogen Balmer-beta (H_β) was selected as a typical emission line from proton auroras, whereas N_2+ 4278 Å, OI 5577 Å and OI 6300 Å emissions were selected for electron auroras. The H_β photometer has a so-called tilting filter to measure rapid space-time variations of faint proton auroras free from the contamination of strong electron auroras. The observations were carried out from March to October 1970 at Syowa Station (corrected geomagnetic lat. -66.7°, long. 72.5°) in Antarctica. From the records of the meridian scanning photometers, spatial distributitions of auroral luminosity along the geomagnetic meridian were displayed as a function of local time, and the iso-intensity contour lines were drawn. These space-time diagrams of auroral luminosity were shown to be very useful for the quantitative study of the dynamic behavior of auroras. Using auroral space-time diagrams, the constitution of the proton and electron aurora substorms was described in detail. During the growth phase of a magnetospheric substorm, the emission zone of the proton aurora moves equatorward with a speed of 100-200m/sec, accompanying the development of the asymmetric ring current and the positive H bay in the evening region. The equatorward movement and the growth of the asymmetric ring current were explained by an earthward movement of the ring current protons due to the intensification of the magnetospheric convection and the subsequent energization of protons through the betatron and Fermi acceleration processes. At the onset of the expansion phase, the quiet arcs suddenly brighten in the pre-midnight region, and the electron aurora bulge rapidly expands poleward and westward, whereas in the post-midnight region, the emission zone of proton auroras rapidly expands poleward and eastward with a large increase in luminosity. Proton auroras are absent in ...